Severity of Burn Injury and the Relationship to Socioeconomic Status in Nova Scotia, Canada. (22nd July 2015) - Le, Jeffrey; Alyouha, Sarah; Liu, Lihui; Bezuhly, Michael; Williams, Jason
Abstract : Objective . Few Canadian studies have examined the relationship between socioeconomic status (SES) and incidence of burn injury. We seek to evaluate this relationship using median income as a measure of SES in Nova Scotia, Canada. Methods . Nova Scotia residents admitted to the Queen Elizabeth II burn unit in Halifax, Nova Scotia, from 1995 to 2012, were included in the study. SES was estimated by linking the subject's postal code to median family household income via Canadian population census data at the level of dissemination areas. Four equal income groups ranging from lowest to highest income quartile were compared (average total burn percentage). Likelihood ratio was calculated to evaluate the effect of median family income burn injury in each income quartile. Results . 302 patients were included in the analysis. Average percent total burn surface area was 19%, 15%, 15%, and 14% (p = 0.18 ) per income quartile (Q1: lowest, Q4: highest), respectively. Likelihood ratios for income quartile Q1–Q4 were 1.3 (0.8–1.6), 1.2 (0.6–1.4), and 0.7 (0.6–1.2), respectively. Conclusion . Contrary to findings in other geographic regions of the world, severity or incidence of burn injury in Nova Scotia, Canada, does not change in relation to SES when using family median income as a surrogate.